Penerapan Fatwa DSN-MUI No. 44/2004 tentang Pembiayaan Multijasa Akad Ijārah Produk Pendidikan - Suci Aurina; Muzayyanah Muzayyanah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This research is motivated by the occurrence of irregularities in the practice of multi-service financing in several Islamic Financial Institutions (IFIs), particularly concerning the disbursement of funds that do not comply with DSN-MUI Fatwa No. 44/DSN-MUI/VIII/2004. The main issue examined is the conformity of multi-service financing practices with sharia principles as well as the implementation of the fatwa in practice. This study employs a qualitative method with a normative-empirical approach through a case study at BMT Al-Fath IKMI, Pamulang District. Primary data were obtained through interviews and observations, while secondary data were collected from institutional documents, the fatwa, and relevant literature on Islamic economic law. The findings reveal, first, that the practice of ijārah multi-service financing in educational products at BMT Al-Fath IKMI complies with the provisions of the fatwa, particularly in terms of service object identification. Second, the determination of ujrah and the contract mechanism also align with sharia principles, thereby maintaining substantive clarity and sharia compliance.